2005
DOI: 10.1111/j.1742-4658.2005.05004.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, cDNA cloning, and expression profiles of the cyclobutane pyrimidine dimer photolyase of Xenopus laevis

Abstract: Photolyase is a light‐dependent enzyme that repairs pyrimidine dimers in DNA. Two types of photolyases have been found in frog Xenopus laevis, one for repairing cyclobutane pyrimidine dimers (CPD photolyase) and the other for pyrimidine–pyrimidone (6–4)photoproduct [(6–4)photolyase]. However, little is known about the former type of the Xenopus photolyases. To characterize this enzyme and its expression profiles, we isolated the entire coding region of a putative CPD photolyase cDNA by extending an EST (expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…We also observed an increase in transcript level of the DNA glycosylase Neil1, which initiates the first step in base excision repair by cleaving bases damaged by oxygen radicals [28]. Furthermore we demonstrate light-induction of a photolyase-like gene, cpd-phr , that removes cyclobutane pyrimidine dimers [29]. ap-1 is light induced in adult zebrafish [12], however it was not detected by the micro-array chip at an early stage of development.…”
Section: Resultsmentioning
confidence: 67%
“…We also observed an increase in transcript level of the DNA glycosylase Neil1, which initiates the first step in base excision repair by cleaving bases damaged by oxygen radicals [28]. Furthermore we demonstrate light-induction of a photolyase-like gene, cpd-phr , that removes cyclobutane pyrimidine dimers [29]. ap-1 is light induced in adult zebrafish [12], however it was not detected by the micro-array chip at an early stage of development.…”
Section: Resultsmentioning
confidence: 67%
“…The induction of CPD photolyase in cultured fish cell lines and in skin or eyes from Xenopus has been reported (Hirayama et al, 2009; Hiroaki et al, 2005; Yasuhira & Yasui, 1992). In plants the induction of cyptochrome genes, including photolyase, has been shown after exposure to blue light wavelengths (Rastogi et al,2010).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, for several experimental aquatic models (frogs and fishes) it has been shown that CPD photolyase transcription is induced upon exposure to visible and blue light wavelengths (Hirayama et al, 2009; Funayama et al 1996). Also, photolyase gene expression in cultured cells, and in the skin for various organisms, has been documented (Rastogi et al, 2010; Hirayama et al, 2009; Hiroaki et al, 2005; Todo et al, 1996; Yasuhira and Yasui, 1992). Given the high conservation of these two genes among vertebrates (Figure 1) and reports indicating photolyases may be expressed in organs other than skin (Hiroaki et al, 2005), we first assessed the general basal expression patterns for the Xiphophorus CPD and 6-4 photolyases in several light responsive external (skin, eyes) and internal (brain, heart, gill, testes, liver) organs.…”
Section: Resultsmentioning
confidence: 99%
“…Since no crystal structure of Xenopus laevis (6–4) photolyase has been reported so far, our initial structure was obtained by homology modeling using the SWISS-MODEL platform . The best fit between the known sequence of Xl (6–4)­PL and that of a protein with a known crystal structure was obtained for the Drosophila melanogaster (6–4)­PL (58% of the amino acid residues are identical and another 21% are chemically similar in the two proteins). The sequence of Xl (6–4)­PL was aligned to the known structure of Dm (6–4)­PL …”
Section: Methodsmentioning
confidence: 99%